FOREIGN DIRECT INVESTMENT AND TECHNOLOGY TRANSFER IN DEVELOPING COUNTRIES: THEORETICAL DISCOURSE - Hamisu Ibrahim (International Studies Journal)
The study of Foreign Direct Investment (FDI) and transfer of technology have been a great interest area for academics, policy makers and industries in both developed and developing countries. There is an increased level of link between foreign direct investment and technology transfer made by multinational corporations in developing countries and it is widely believed that FDI help to transfer technology to the benefit of the domestic industries and host country. The general objective of the study is to examine whether FDI have impacted positively to technology transfer in developing countries, and the major source of data for this study is the secondary source. But the examination shows that FDI by multinationals brings capital into the economy, new technologies, new methods of doing  business, new skills and increases the set of employment opportunities available to local workers. In addition, FDI helps the host country to build and / or expand various networks such as procurement and marketing networks and above all increases the host country’s foreign exchange earnings and balance of payments through export expansion. However, this study shows that this benefit does not automatically accrue to the host country but rather technology is transferred to host industries with strong absorptive capability through technological spill overs rather than via direct effect. Based on the examination, the following suggestions were made; that the host country should strengthen the fundamentals of economy by pursuing policies to enhance the supply of modern infrastructure and appropriately trained workers, by achieving greater macro-economic and political stability.